THEORETICAL, ECONOMIC AND METHODOLOGICAL BASIS OF PROPERTY INSURANCE - Tuxtarova Maftuna Yo‘ldoshboy kizi (American Journals, 2024)
In this article, the theoretical, economic, and methodological foundations of property insurance, as well as suggestions and practical recommendations for the implementation of property insurance relations and further improvement of insurance relations have been developed.
Keywords: Commercial banks, insurance organizations, insurance market, bank insurance, insurance premium, insurance money, insurance liability.